Drill bit failure in Mandible fracture Fixation- A case report and Management - Ulaganathan, Prabhakar (Journal of Orofacial Research, 2025)
Drill bit breakage during maxillofacial surgical procedures, including open reduction and internal fixation of mandible fractures, is a common but challenging complication for surgeons. While immediate retrieval is often successful, some cases require a more complex approach. This case report describes a retained drill bit fragment encountered during the fixation of mini plates and screws in a patient with a mandibular fracture. The article explores the multifaceted factors contributing to drill bit failure, encompassing drill bit characteristics, surgical technique, patient anatomy, and surgeon-related factors. Additionally, it covers techniques for removing broken drill bits and examines the decision-making process and potential issues. By examining both the causes and management of drill bit breakage, the article aims to guide surgeons in addressing this challenge.